2012
DOI: 10.2337/db11-1402
|View full text |Cite
|
Sign up to set email alerts
|

Perilipin 2 Improves Insulin Sensitivity in Skeletal Muscle Despite Elevated Intramuscular Lipid Levels

Abstract: Type 2 diabetes is characterized by excessive lipid storage in skeletal muscle. Excessive intramyocellular lipid (IMCL) storage exceeds intracellular needs and induces lipotoxic events, ultimately contributing to the development of insulin resistance. Lipid droplet (LD)–coating proteins may control proper lipid storage in skeletal muscle. Perilipin 2 (PLIN2/adipose differentiation–related protein [ADRP]) is one of the most abundantly expressed LD-coating proteins in skeletal muscle. Here we examined the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
148
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(165 citation statements)
references
References 49 publications
12
148
1
4
Order By: Relevance
“…These relationships support our previous findings that highlight the role of PGC1a in the regulation of intramuscular lipid droplet programming in mice and humans (23). Finally, we focused on expression levels of the lipid droplet coat proteins PLIN5, PLIN3, and PLIN2 as well as the lipolytic protein ATGL in both muscle tissue and myotubes because we have previously shown in animal studies that overexpressing PLIN2 or PLIN5 increases TAG storage capacity and results in the prevention of high-fat-induced insulin resistance (40,46). In the current study, we found that PLIN5 was elevated in the muscle tissue of the T2D individuals but not in their myotubes.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…These relationships support our previous findings that highlight the role of PGC1a in the regulation of intramuscular lipid droplet programming in mice and humans (23). Finally, we focused on expression levels of the lipid droplet coat proteins PLIN5, PLIN3, and PLIN2 as well as the lipolytic protein ATGL in both muscle tissue and myotubes because we have previously shown in animal studies that overexpressing PLIN2 or PLIN5 increases TAG storage capacity and results in the prevention of high-fat-induced insulin resistance (40,46). In the current study, we found that PLIN5 was elevated in the muscle tissue of the T2D individuals but not in their myotubes.…”
Section: Discussionsupporting
confidence: 65%
“…IMCL content inversely correlates with peripheral insulin sensitivity (34-37), suggesting that fat accumulation (38,39). Other studies have even suggested that increasing the TAG storage capacity, specifically in skeletal muscle, may be beneficial (40)(41)(42). Although these studies used different methods (i.e., genetic manipulations, exercise), they clearly demonstrated a beneficial effect of increased TAG storage on skeletal muscle insulin sensitivity.…”
Section: Discussionmentioning
confidence: 91%
“…Os fatores NRF1 e 2 são requeridos para a biogênese mitocondrial e os receptores nucleares alfa relacionados ao estrogênio (EERα) induzem a expressão de genes que regulam a fosforilação oxidativa, biogênese mitocondrial e a síntese de ATP. Ambos, fatores NRF1, NRF2 e receptores EERα, mostraram-se elevados no tecido muscular em resposta a oxidação de ácidos graxos 49 54 . A proteína PLIN2 é essencial para o estoque de triglicérides intramusculares e inibição da lipólise 54 .…”
Section: Regulação Molecular Do Músculo Esquelético Ao Exercício Aeróunclassified
“…Ambos, fatores NRF1, NRF2 e receptores EERα, mostraram-se elevados no tecido muscular em resposta a oxidação de ácidos graxos 49 54 . A proteína PLIN2 é essencial para o estoque de triglicérides intramusculares e inibição da lipólise 54 . Sendo, portanto, a expressão das proteínas PLIN2 e PLIN5 altamente reguladas no exercício aeróbico.…”
Section: Regulação Molecular Do Músculo Esquelético Ao Exercício Aeróunclassified
See 1 more Smart Citation